Identifying patterns and sources of anthropogenic trace metals in the Argentine Central Andes by using snow samples and an atmospheric dispersion model - Ruggeri, María Florencia (2020)
This study presents the first local measurements of metals in snow from the Argentine Central Andes. Cu, Pb and Zn were selected as specific tracers of anthropogenic local emission sources in the study area. Snow samples were collected during winter (2014, 2015 and 2016) at two sites with different characteristics: Punta de Vacas and Vallecitos. The samples were analyzed by ICP-MS, and the average concentrations found were 1.4 μg L-1 (Cu), 2.2 μg L-1 (Pb) and 14.2 μg L-1 (Zn) in the snow samples from Vallecitos, and 5.3 μg L-1 (Cu), 2.6 μg L-1 (Pb) and 24.0 μg L-1 (Zn) in the snow samples from Punta de Vacas. These data and the snowfall amount in each sampling site were statistically analyzed. Results suggested that the levels of metals in the snow are influenced not only by the atmospheric concentrations, but also by the amount of precipitated snow. Additionally, an atmospheric dispersion model, CALPUFF, was applied in the study area to determine the origin of the studied metals and to understand the spatial distribution pattern of the concentrations found. Results showed that the metal atmospheric loads in the study area originated from local sources, especially vehicular traffic and mining. This work represents an important contribution to the knowledge and preservation of the local Andean cryosphere, and it could be used as an input to develop protection policies in the area through the combination of different and complementary tools for the evaluation of air quality.